2021
DOI: 10.21037/cdt-20-518
|View full text |Cite
|
Sign up to set email alerts
|

MiR-155 acts as an inhibitory factor in atherosclerosis-associated arterial pathogenesis by down-regulating NoxA1 related signaling pathway in ApoE−/− mouse

Abstract: Background: To investigate the protective efficacy of miR-155 on down regulating NADPH oxidase isoform subunit A1 (NoxA1) gene expression, resulting in inhibition of VSMC migration and over proliferation and thus ameliorating the progression of arterial atherosclerosis in AS mouse model. Therefore, to further explore the regulatory effect of miR-155 on neointima formation in AS and locate potential antiatherosclerosis target. Methods: The mouse vascular aorta smooth muscle cell (MOVAS) was cultured and transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(24 reference statements)
1
3
0
Order By: Relevance
“…Zheng et al ( 150) found miR-155 encapsulated in KLF5induced exosomes from VSMCs to ECs, which destroyed the integrity of endothelial barriers, resulting in AS. This result is consistent with the research mentioned above that elevated miR-155 enhanced AS progress (54,(151)(152)(153)(154). González et al (144) suggested that miR-155-5p might be implicated in plaque instability by targeting AKT, contributing to AS.…”
Section: Mirnas Encapsulated In Vsmc-evs Regulate the Process Of Assupporting
confidence: 93%
See 1 more Smart Citation
“…Zheng et al ( 150) found miR-155 encapsulated in KLF5induced exosomes from VSMCs to ECs, which destroyed the integrity of endothelial barriers, resulting in AS. This result is consistent with the research mentioned above that elevated miR-155 enhanced AS progress (54,(151)(152)(153)(154). González et al (144) suggested that miR-155-5p might be implicated in plaque instability by targeting AKT, contributing to AS.…”
Section: Mirnas Encapsulated In Vsmc-evs Regulate the Process Of Assupporting
confidence: 93%
“…MiR-155 activated the NLRP3 by regulating NF-κB in the AS progression of ApoE (−/−) mice ( 155 ). However, evidence showed that miR-155 exerted inhibition on AS in ApoE (−/−) mice ( 156 ). Park et al ( 157 ) suggested that miR-155 was a novel negative regulator in the soluble guanylyl cyclase (sGC)/cGMP pathway, providing a novel therapeutic target for AS.…”
Section: The Flexibility and Versatility Of Mirnas Encapsulated In Vs...mentioning
confidence: 99%
“…As shown in Fig. 7, CFTR, CDK1, RPS13, RPS15A, RPS27, NOTCH1, MRPL12, NOS2, CCDC85B and ATN1 achieved an AUC value of >0.88, demonstrating NOXA1 [76] are involved in progression of atherosclerosis. A previous study reported that S100A9 [77], ADORA3 [78], IL1R2 [79], FPR1 [80], CCL20 [ [96], AQP4 [97], FCER1G [98], CCL18 [99], HP (haptoglobin) [100], CDK1 [101], SLC7A11 [102], CFTR (CF transmembrane conductance regulator) [103], F8 [104], STC1 [44], IL18RAP [90], TIMP3 [105], PDE4D [106], CYP4A11 [107], SCN10A [108], APOB (apolipoprotein B) [109], ACE (angiotensin I converting enzyme) [110], PENK (proenkephalin) [111], HSPB6 [112], TLR9 [113], EGR1 [114], CACNG8 [115], FOXD3 [116], DBH (dopamine beta-hydroxylase) [117], FOXP3 [118] [189], MAOA (monoamine oxidase A) [190], BMPR1B (bone morphogenetic protein receptor type 1B) [191], FGF7 [192], CALCRL (calcitonin receptor like receptor) [193], MARK3 [194], ADH1B [195], AMH (anti-Mullerian hormone) [196], RET (ret proto-oncogene) [197], IGF2 [198], SLC6A9 [199], NPPA (natriuretic peptide A) [200], SCT (secretin) [201], DCX (doublecortin) …”
Section: Validation Of Hub Genes By Receiver Operating Characteristic Curve (Roc) Analysismentioning
confidence: 77%
“…Immune system [46], innate immune system [47], neutrophil degranulation [48], toll-like receptor cascades [49], metabolism of amino acids and derivatives [50], neuronal system [51], extracellular matrix organization [52], degradation of the extracellular matrix [53], diseases of glycosylation [54], response to stimulus [55], cell communication [56], cell periphery [57], membrane [58], anatomical structure development [59] and plasma membrane [60] were responsible for progression of MI. PLA2G2A [61], CCL23 [62], CD53 [63], TREML4 [64], TREM2 [65], CD180 [66], HPSE (heparanase) [67], CELA2A [68], TNFRSF4 [69], AMBP (alpha-1-microglobulin/bikunin precursor) [70], SOX18 [71], PANX2 [72], RSPO2 [73], COMP (cartilage oligomeric matrix protein) [74], ASGR1 [75] and NOXA1 [76] are involved in progression of atherosclerosis. A previous study reported that S100A9 [77], ADORA3 [78], IL1R2 [79], FPR1 [80], CCL20 [81], CD163 [82], S100A8 [83], TLR2 [84], HAS2 [85], PTX3 [86], TIMP4 [87], AREG (amphiregulin) [88], LBP (lipopolysaccharide binding protein) [89], IL18R1 [90], ALOX5AP [91], RETN (resistin) [92], F13A1 [93], FPR2 [94], SAA1 [95], FLT3 [96], AQP4 [97], FCER1G [98], CCL18 [99], HP (haptoglobin) [100], CDK1 [101], SLC7A11 [102], CFTR (CF transmembrane conductance regulator) [103], F8 [104], STC1[44], IL18RAP [90], TIMP3 [105], PDE4D [106], CYP4A11 [107], SCN10A [108], APOB (apolipoprotein B) [109], ACE (angiotensin I converting enzyme) [110], PENK (proenkephalin) [111], HSPB6 [112], TLR9 […”
Section: Discussionmentioning
confidence: 99%